Comparative analysis of analytical and graphical upperbound solutions for 4-high reversing aluminium cold-rolling sheet mill (2012)
Upper bound solutions to a 4-High reversing aluminium cold-rolling sheet mill was obtained in this work using both analytical and graphical methods. The upper bound method was applied to the rolling of an Al 1200 sheet from 7mm to 0.6mm in six passes. It was observed that both methods were very effective in predicting upper bound load value with the graphical method giving a higher value using input velocity values from industry. However, it was observed that the graphical method becomes very difficult to use when sheet thicknesses become very small.